Penerapan Arsitektur Neo Vernakular pada Museum Geopark Batur - Nurwahid A, Latif (Universitas Medan Area, 2025)
In an increasingly advanced era of development, many public buildings are starting to abandon traditional or local elements in their designs. This can lead to cultural extinction or degradation, therefore an approach is needed that can preserve and revive the cultural values of an area. One solution is the Neo Vernacular Architecture approach, which elevates the values of Traditional Architecture into a more modern form. One example of a building that applies Neo Vernacular Architecture is the Batur Geopark Museum. The purpose of this study was to determine the criteria, characteristics, and principles of implementing Neo Vernacular Architecture in the Batur Geopark Museum building. This study uses a qualitative descriptive method with a literature study approach, document studies and data analysis, which is in accordance with the criteria, characteristics, and principles of the form of Neo Vernacular Architecture. The results will be arranged in detail so as to obtain an answer that the Batur Geopark Museum applies some of the Neo Vernacular criteria, characteristics and principles in a design.